A Digital Cost Management Competency Framework for Quantity Surveying Education: Integrating BIM 5D with Project-Based Learning - Song, Jiaqi (Journal of Educational Research and Policies, 2026)
The digital transformation of the construction industry has created growing demand for quantity surveyors with competencies in Building Information Modelling (BIM) and digital cost management. However, traditional quantity surveying education remains largely focused on theoretical instruction and software-oriented training, limiting students' ability to apply digital technologies in authentic engineering practice. This study proposes the Digital Cost Management Competency Framework (DCMCF), which integrates BIM 5D, Project-Based Learning (PBL), and competency-oriented assessment into quantity surveying education. A mixed-methods case study was conducted using two cohorts of students enrolled in an Engineering Quantity Measurement and Valuation course at a public higher vocational institution in China. Quantitative data were collected from students' academic performance, while qualitative evidence was obtained through classroom observations, project deliverables, and teaching reflections. Evaluation results indicated that students demonstrated a more comprehensive grasp of BIM operations and digital literacy. The PBL approach also led to more active peer discussions and tactical problem-solving when students were confronted with discrepant quantity take-offs. Compared with the previous cohort, students demonstrated improved performance, particularly in competency-oriented assessment and practical learning activities. The study offers a practical framework and empirical evidence for competency-oriented reform in quantity surveying education.